Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5005/jp-journals-10071-23635
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis for Pulmonary Hemorrhage Following Viperine Snakebite: Case Report with Review of Literature

Abstract: A bstract Introduction Snakebites are one of the commonest occupational hazards in tropical countries and viperine bites are potential to cause systemic toxicity. Coagulopathies and acute kidney injury (AKI) have been documented and easily dealt with in past, but pulmonary hemorrhage has been rarely seen and plasmapheresis has shown promising result for the same. This case reports highlight the effective use of plasmapheresis for pulmonary hemorrhage post-snakebite. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…9,10 Viper venom is hemovasculotoxic, causing endothelial dysfunction and bleeding due to coagulopathy and thrombocytopenia. 11 Our patient had coagulopathy requiring extensive transfusion support, AKI requiring renal replacement therapy, and, later, lower-limb weakness, with inability to mobilize, resulting in 50 d of hospital stay, all following a single devastating snakebite event. His weakness occurred because of compression of the lumbosacral plexus and related nerves by a hematoma formed owing to persistent and delayed coagulopathy as a result of antivenom ineffectiveness.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…9,10 Viper venom is hemovasculotoxic, causing endothelial dysfunction and bleeding due to coagulopathy and thrombocytopenia. 11 Our patient had coagulopathy requiring extensive transfusion support, AKI requiring renal replacement therapy, and, later, lower-limb weakness, with inability to mobilize, resulting in 50 d of hospital stay, all following a single devastating snakebite event. His weakness occurred because of compression of the lumbosacral plexus and related nerves by a hematoma formed owing to persistent and delayed coagulopathy as a result of antivenom ineffectiveness.…”
Section: Discussionmentioning
confidence: 84%
“…9,10 Viper venom is hemovasculotoxic, causing endothelial dysfunction and bleeding due to coagulopathy and thrombocytopenia. 11…”
Section: Discussionmentioning
confidence: 99%
“…Viper venom is hemo-vasculotoxic, with hemorrhagins and hemolysins causing endothelial dysfunction and bleeding. 3 Echis carinatus (saw-scaled viper) venom is known to contain potent toxins such as snake venom metalloproteinases, phospholipase A2, and snake lectins, which interfere with coagulation pathway and platelet action. 4 Supportive care includes blood product transfusions, wound care, and renal replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However they did not specifically describe the symptoms and disease spectrum. Sampley et al 3 reported DAH in viper envenoming during the first week, with a normal coagulation profile managed with methylprednisolone and plasmapheresis. Srirangan et al 14 reported the successful use of plasmapheresis and methylprednisolone in DAH on day 3 of a hump-nosed pit viper bite, with coagulopathy and thrombotic microangiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In India, one patient survived severe envenomation from a Daboia russelli but developed consumptive coagulopathy, acute renal failure, rhabdomyolysis, paralysis, and diffuse alveolar hemorrhage persisting a week after the bite. Plasmapheresis was proposed to aid the patient's recovery [ 34 ].…”
Section: Impaired Normal Cell Functions and Integritymentioning
confidence: 99%